ChemInform Abstract: Organocatalytic, Oxidative, Intermolecular Amination and Hydrazination of Simple Arenes at Ambient Temperature. Issue 14 (20th March 2013) - Samanta, Rajarshi; Bauer, Jonathan O.; Strohmann, Carsten; Antonchick, Andrey P.
Abstract A new, mild, efficient, and environmentally friendly method renders possible the preparation of anilines and aromatic hydrazines from non‐prefunctionalized arenes.